LSEC Fenestrae Are Preserved Despite Pro-inflammatory Phenotype of Liver Sinusoidal Endothelial Cells in Mice on High Fat Diet - Kus, Edyta; Kaczara, Patrycja; Czyzynska-Cichon, Izabela; Szafranska, Karolina; Zapotoczny, Bartlomiej; Kij, Agnieszka; Sowinska, Agnieszka; Kotlinowski, Jerzy; Mateuszuk, Lukasz; Czarnowska, Elzbieta; Szymonski, Marek; Chlopicki, Stefan (Frontiers in Physiology, 2019)
Healthy liver sinusoidal endothelial cells (LSECs) maintain liver homeostasis, while LSEC dysfunction was suggested to coincide with defenestration. Here, we have revisited the relationship between LSEC pro-inflammatory response, defenestration, and impairment of LSEC bioenergetics in non-alcoholic fatty liver disease (NAFLD) in mice. We characterized inflammatory response, morphology as well as bioenergetics of LSECs in early and late phases of high fat diet (HFD)-induced NAFLD. LSEC phenotype was evaluated at early (2–8 week) and late (15–20 week) stages of NAFLD progression induced by HFD in male C57Bl/6 mice. NAFLD progression was monitored by insulin resistance, liver steatosis and obesity. LSEC phenotype was determined in isolated, primary LSECs by immunocytochemistry, mRNA gene expression (qRT-PCR), secreted prostanoids (LC/MS/MS) and bioenergetics (Seahorse FX Analyzer). LSEC morphology was examined using SEM and AFM techniques. Early phase of NAFLD, characterized by significant liver steatosis and prominent insulin resistance, was related with LSEC pro-inflammatory phenotype as evidenced by elevated ICAM-1, E-selectin and PECAM-1 expression. Transiently impaired mitochondrial phosphorylation in LSECs was compensated by increased glycolysis. Late stage of NAFLD was featured by prominent activation of pro-inflammatory LSEC phenotype (ICAM-1, E-selectin, PECAM-1 expression, increased COX-2, IL-6, and NOX-2 mRNA expression), activation of pro-inflammatory prostaglandins release (PGE2 and PGF2α) and preserved LSEC bioenergetics. Neither in the early nor in the late phase of NAFLD, were LSEC fenestrae compromised. In the early and late phases of NAFLD, despite metabolic and pro-inflammatory burden linked to HFD, LSEC fenestrae and bioenergetics are functionally preserved. These results suggest prominent adaptive capacity of LSECs that might mitigate NAFLD progression.